Epigenetic mechanisms of alveolar macrophage activation in chemical-induced acute lung injury - Ahmad, Shama; Nasser, Wesam; Ahmad, Aftab (Frontiers in Immunology, 2024)
Airways, alveoli and the pulmonary tissues are the most vulnerable to the external environment including occasional deliberate or accidental exposure to highly toxic chemical gases. However, there are many effective protective mechanisms that maintain the integrity of the pulmonary tissues and preserve lung function. Alveolar macrophages form the first line of defense against any pathogen or chemical/reactant that crosses the airway mucociliary barrier and reaches the alveolar region. Resident alveolar macrophages are activated or circulating monocytes infiltrate the airspace to contribute towards inflammatory or reparative responses. Studies on response of alveolar macrophages to noxious stimuli are rapidly emerging and alveolar macrophage are also being sought as therapeutic target. Here such studies have been reviewed and put together for a better understanding of the role pulmonary macrophages in general and alveolar macrophage in particular play in the pathogenesis of disease caused by chemical induced acute lung injury. Deleted: However, there are many effective protective 40 mechanisms that maintain the integrity of the pulmonary tissues and 41 preserve lung function 474 475 476 Formatted: Font: (Default) Times New Roman Deleted: Details of all funding sources should be provided, 477 including grant numbers if applicable. Please ensure to add all 478 necessary funding information, as after publication this is no longer 479 possible. ¶ 480 Acknowledgments ¶ 481 This is a short text to acknowledge the contributions of specific 482 colleagues, institutions, or agencies that aided the efforts of the 483 authors. ¶ 484